2018
DOI: 10.1016/j.rbmo.2018.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Predicting live birth for poor ovarian responders: the PROsPeR concept

Abstract: This model, specific to PORs receiving r-hFSH, constitutes the best compromise between precision and simplicity, and is suitable for routine practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…There were no differences observed in efficacy outcomes (number of oocytes retrieved [primary endpoint]; biochemical pregnancy rate, CPR, OPR; and LBR) between patients receiving r-hFSH/r-hLH and those receiving r-hFSH alone. However, a post-hoc analysis of the ESPART study observed a higher live birth rate with r-hLH supplementation in patients with moderate or severe POR, while a higher live birth rate was observed with r-hFSH alone in patients with mild POR (130).…”
Section: Recombinant Gonadotropinsmentioning
confidence: 99%
“…There were no differences observed in efficacy outcomes (number of oocytes retrieved [primary endpoint]; biochemical pregnancy rate, CPR, OPR; and LBR) between patients receiving r-hFSH/r-hLH and those receiving r-hFSH alone. However, a post-hoc analysis of the ESPART study observed a higher live birth rate with r-hLH supplementation in patients with moderate or severe POR, while a higher live birth rate was observed with r-hFSH alone in patients with mild POR (130).…”
Section: Recombinant Gonadotropinsmentioning
confidence: 99%
“…Furthermore, the ESHRE Bologna criteria do not aim to differentiate between oocyte quality and oocyte quantity; instead aiming to identify a homogenous population with reduced ovarian reserve, rather than a population with similar prognoses for pregnancy [41]. Despite these shortcomings, we propose that poor responders are defined according to the Bologna criteria, as analyses suggest they are clinically relevant [43]. Therefore, poor responders are patients from whom we would expect to retrieve 3 oocytes after conventional COS.…”
Section: Ovulatory Women (Including Women With Unexplained Infertilitmentioning
confidence: 99%
“…The aim of these tools is to provide an objective recommendation for embryologists, enabling the standardization of treatment across different centers by removing operator variability/subjectivity. This is an important goal, as center effect and operator variability are major contributors to differences in treatment outcomes for fertility treatment [43,71]. These tools are being designed to work together with the automation of key steps in the embryo lab (e.g.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…As women are increasingly deferring family building into more advanced reproductive ages, with the associated compromised ovarian reserve, correct predictions of pregnancy chances become even more important in counseling patients with a more unfavorable prognosis ( Lehert et al , 2018 ). Our academically affiliated fertility center serves a population of infertile women with a very high prevalence of diminished ovarian reserve (DOR), mostly related to advanced female age or premature ovarian aging (POA) ( Gleicher et al , 2015 ).…”
Section: Introductionmentioning
confidence: 99%